PRODUKTIVITAS SOM JAWA (Talinum paniculatum Gaertn.) PADA BEBERAPA KOMPOSISI BAHAN ORGANIK - DARWATI, IRENG; RAHARDJO, MONO; SMD, ROSITA (Jurnal Penelitian Tanaman Industri, 2000)
Productivity of Talinum paniculatum Gaertn. on several of organ ics matter compositionTalinum paniculatum Gaertn. is a tuber producing crop To produce (he optimum yield Ihe crop needs the soil with good physical properties and fertility The soil conditions may be improved by applying organic matter. An experiment was conducted to evaluate Ihe effect of the composition of organic matter (compost, stable manure and casting) on tuber yield of talinum. The experiment was carried out at the Research Institute for Spice and Medicinal Crop. Bogor. from September 1996 to September 1997. in a randomized block designed with four replications. The treatments evaluated were Ihe ratio of soil organic matter, i.e (I) soil, (2) soil + stable manure (3:1); (3) soil + casting (3:1); (4) soil + bamboo leaf compost (3:1): (5) soil + casting + bamboo leaf compost (6:1:1); (6) soil + stable manure + bamboo leaf compost (6:1:1); (7) soil + stable manure â™¦ casting (6:1:1). Seedling was planted in polybag containing 20 kg of tested media Plants were applied with I g urea, 3 g TSP and 3 g KCI/polybag as basal dressing, while 2 g of urea was applied as top dressing at 3 months after planting. Plants were harvested at I year after planting Result of experiment found thai 3 kinds of organic matter treatments could increase Ihe number, fresh weight, and dry weight of tuber The highest tuber production were 165.40 g fresh/plant and 26.75 g dried/plant resulted from soil and casting treatment (3 I).